A REVIEW ON DEEP LEARNING ALGORITHMS FOR SPEECH AND FACIAL EMOTION RECOGNITION - Latha, Charlyn Pushpa; Priya, Mohana (APTIKOM Publisher, 2016)
Deep Learning is the recent machine learning technique that tries to model high level abstractions in databy using multiple processing layers with complex structures. It is also known as deep structured learning,hierarchical learning or deep machine learning. The term ?deep learning